(untitled) (Research, Society and Development, 2022)
Objective: To identify how the practice of critical nursing care is given to patients undergoing cardiopulmonary bypass. Methodology: This is a literature review, following the guidelines recommended by the Preferred Reporting Items Systematic Reviews and Meta-Analyses (PRISMA) and organized in the following steps: elaboration of the review protocol; data collection with the inclusion of publications that brought contributions and answers relevant to the research question; extraction of information contained in the study; analysis and interpretation of data; and, finally, presentation and discussion of the review. Results and discussion: Initially, 137 articles were selected in the databases and after a thorough selection, 12 articles remained to compose the results. Descriptive, retrospective and cohort studies are part of this sample. After analyzing the data, it was observed that only half of the ICUs had professionals with experience in ECMO and only 46% of nurses were able to independently care for patients on VV-ECMO. This shows us that the number of experienced and trained intensive care nurses is low, which causes an overload of these professionals. Along with experience, continuing and standardized education is necessary to increase the number of professionals who can handle this highly complex therapy. Conclusion: According to the studies analyzed, we found that ECMO is considered a technique increasingly present in the care of the person in a critical situation in need of mechanical cardiopulmonary support in situations of severe respiratory failure, heart failure or both.